Analisis Strategi Komunikasi Pemasaran Terpadu Bioskop Platinum Cineplex Cibinong Square Dalam Menarik Minat Menonton Di Tengah Maraknya Video Streaming - Maulana, Egy Gilang; Martha, Layung Paramesti; Kusumaninngtias, Intan Tri (Universitas Al Azhar Indonesia, 2022)
The phenomenon of closing cinemas during the Covid-19 pandemic changed the kebiasaans of some people in watching films. In the current new normal era, cinemas are gradually recovering to attract interest in watching amidst the rise of video streaming. This study aims to analyze the marketing communication strategy using Integrated Marketing Communication (IMC) at the Platinum Cineplex Cibinong Square cinema in attracting interest in watching amidst the rise of video streaming and to find out what obstacles and solutions are encountered in implementing the integrated marketing communication component. This research combines emic and etic perspectives. The data collection technique in this study was by conducting in-depth interviews, field observations, and checking the validity of the data using source triangulation.. The results in this study indicate that the integrated marketing communication strategy at the Platinum Cineplex Cibinong Square cinema in attracting interest in watching amidst the rise of video streaming uses eight promotion mix components, namely, (1) direct marketing, (2) sales promotion, (3) public relationss, (4) personal selling, (5) advertising, (6) word of mouth marketing, (7) events and experiences, (8) interactive marketing.